2021
DOI: 10.21608/epsj.2021.195785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed Restriction Regimen on Productive Performance and Economical Efficiency of Weaning NZW Rabbits

Abstract: This experiment aimed to study the effects of feed restriction (FR) on weaning New Zealand White Rabbit's growth performance. Seventy-five unsexed rabbits (5 weeks of age) were divided to five experimental treatments with five equal replications. Feed restriction program was used in the first two weeks (5-7 weeks old) after weaning as follows; the first treatment (control) was free fed the experimental diet. While other treatments (2 to 5) were fed restricted diets at levels of 10, 20, 30 and 40%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Tumova et al, (2003) demonstrated that FBW of rabbits did not affect by feed restriction. Sara (2021) found that EE values were significantly high when feed restricted by 40% compared with control group. Romero et al (2010) observed that rabbits exposed to feed restriction (fed 8 hours daily at 2 weeks after weaning) had low mortality rate because of feed restriction reduced bloated abdomen, relatively low body weight, diarrhea.…”
Section: Economic Evaluationmentioning
confidence: 82%
“…Tumova et al, (2003) demonstrated that FBW of rabbits did not affect by feed restriction. Sara (2021) found that EE values were significantly high when feed restricted by 40% compared with control group. Romero et al (2010) observed that rabbits exposed to feed restriction (fed 8 hours daily at 2 weeks after weaning) had low mortality rate because of feed restriction reduced bloated abdomen, relatively low body weight, diarrhea.…”
Section: Economic Evaluationmentioning
confidence: 82%